A comprehensive and consistent mineral dissolution rate database: Part II: Secondary silicate minerals - Matylda Heřmanská; Martin J. Voigt; Chiara Marieni; Julien Declercq; Eric H. Oelkers (Chemical Geology, 2023)

Chemical and Water-Isotope Composition Unravels the Source and Evolution of the Kittilä Underground Mine Water, Kiistala, Finland - V. Milesi; J. Declercq; W. Harding; T. Jarman; O. Baas; J. Saukkoriipi; A. van Wageningen; R. Bowell (Mine Water and the Environment, 2023)

Correction to: Lifestyle factors and lung cancer risk among never smokers in the Canadian Partnership for Tomorrow’s Health (CanPath) - Rachel A. Murphy; Maryam Darvishian; Jia Qi; Yixian Chen; Quincy Chu; Jennifer Vena; Trevor J. B. Dummer; Nhu Le; Ellen Sweeney; Vanessa DeClercq; Scott A. Grandy; Melanie R. Keats; et al. (Cancer Causes & Control, 2022)

Lifestyle factors and lung cancer risk among never smokers in the Canadian Partnership for Tomorrow’s Health (CanPath) - Rachel A. Murphy; Maryam Darvishian; Jia Qi; Yixian Chen; Quincy Chu; Jennifer Vena; Trevor J. B. Dummer; Nhu Le; Ellen Sweeney; Vanessa DeClercq; Scott A. Grandy; Melanie R. Keats; et al. (Cancer Causes & Control, 2022)

The relationship between anthropometric measures and cardiometabolic health in shift work: findings from the Atlantic PATH Cohort Study - Ellen Sweeney; Zhijie Michael Yu; Trevor J. B. Dummer; Yunsong Cui; Vanessa DeClercq; Cynthia Forbes; Scott A. Grandy; Melanie Keats; Louise Parker; Anil Adisesh (International Archives of Occupational and Environmental Health, 2020)

Influence of the bordering shelves on nutrient distribution in the Arctic halocline inferred from water column nitrate isotopes - F. Fripiat; M. Declercq; C. J. Sapart; L. G. Anderson; V. Bruechert; F. Deman; D. Fonseca‐Batista; C. Humborg; A. Roukaerts; I. P. Semiletov; F. Dehairs (Limnology and Oceanography, 2018)
The East Siberian Sea and contiguous western Arctic Ocean basin are characterized by a subsurface nutrient maximum in the halocline, generally attributed to both Pacific inflow and intensive remineralization in shelf bottom waters that are advected into the central basin. We report nitrogen and oxygen isotopic measurement of nitrate from the East Siberian Sea and western Eurasian Basin, in order to gain insight into how nitrate is processed by the microbial community and redistributed in the Arctic Ocean. A large decoupling between nitrate δ 15 N and δ 18 O is reported, increasing and decreasing upward from the Atlantic temperature maximum layer toward the surface, respectively. A correlation between water and nitrate δ 18 O indicates that most of the nitrate (> 60%) at the halocline has been regenerated within the Arctic Ocean. The increase in nitrate δ 15 N correlates with the fixed N deficit, indicating a causal link between the loss of fixed N and the 15 N enrichment. This suggests that a significant share of benthic denitrification is driven by nitrate supplied by remineralization and partial nitrification, allowing residual 15 N‐enriched ammonium to diffuse out of the sediments. By increasing nutrient concentrations and fixed N deficit in shelf bottom waters, this imprint is attenuated offshore following advection into the halocline by nitrate regeneration and mixing. Estimation of the sedimentary isotope effect related to benthic denitrification yields values in the range of 2.4–3.8‰, with its magnitude driven by both the degree of coupling between remineralization and nitrification, and fixed N concentrations in shelf bottom waters.

First isolation of Vibrio tapetis and an atypical strain of Aeromonas salmonicida from skin ulcerations in common dab ( Limanda limanda ) in the North Sea - M Vercauteren; E De Swaef; A Declercq; L Bosseler; S Gulla; S Balboa; J L Romalde; L Devriese; H Polet; F Boyen; K Chiers; A Decostere (Journal of Fish Diseases, 2018)
Skin ulcerations rank amongst the most prevalent lesions affecting wild common dab ( Limanda limanda ) with an increase in prevalence of up to 3.5% in the Belgian part of the North Sea. A complex aetiology of these ulcerations is suspected, and many questions remain on the exact factors contributing to these lesions. To construct the aetiological spectrum of skin ulcerations in flatfish, a one‐day monitoring campaign was undertaken in the North Sea. Fifteen fish presented with one or more ulcerations on the pigmented and/or non‐pigmented side. Pathological features revealed various stages of ulcerations with loss of epidermal and dermal tissue, inflammatory infiltrates and degeneration of the myofibers bordering the ulceration, albeit in varying degrees. Upon bacteriological examination, pure cultures of Vibrio tapetis were retrieved in high numbers from five fish and of Aeromonas salmonicida in one fish. The V. tapetis isolates showed cross‐reactivity with the sera against the representative strain of serotype O2 originating form a carpet‐shell clam ( Ruditapes descussatus ). Moreover, the A. salmonicida isolates displayed a previously undescribed vapA gene sequence (A‐layer type) with possible specificity towards common dab. Further research is necessary to pinpoint the exact role of these agents in the development of skin ulcerations in common dab.

Isolation and characterization of Pseudomonas syringae pv. porri from leek in Flanders - S. Rombouts; J. Van Vaerenbergh; A. Volckaert; S. Baeyen; T. De Langhe; B. Declercq; R. Lavigne; M. Maes (European Journal of Plant Pathology, 2016)

β-Alanine does not act through branched-chain amino acid catabolism in carp, a species with low muscular carnosine storage - F. Geda; A. Declercq; A. Decostere; A. Lauwaerts; B. Wuyts; W. Derave; G. P. J. Janssens (Fish Physiology and Biochemistry, 2015)

Molecular characterization of Phytophthora porri and closely related species and their pathogenicity on leek (Allium porrum) - B. Declercq; E. Van Buyten; S. Claeys; N. Cap; J. De Nies; S. Pollet; M. Höfte (European Journal of Plant Pathology, 2010)